Assessment of Firm-Level Skills Demand and Engagement in Skills Development : Creating a Demand-Led Skills Ecosystem in Moldova - International Finance Corporation (Washington, DC, 2017)
The objective of this research is to provide analysis on the current skills ecosystem in Moldova. This assessment is based on interviews with private sector representatives, training providers and government representatives, and desk research. The report presents its findings on skills demand and skills mismatches, the private sector’s human resource management (HRM) practices and workforce development approaches, the education system and workforce training, and possibilities to strengthen future skills-forecasting practices in Moldova. The research is intended to provide ideas for strengthening structured private-sector engagement in skills development activities in the future to ensure the prevalence of demand-led and demand-responsive skills development initiatives. Additional information on the relevant legal framework governing labor and education, sectoral and education committees, and an overview of the education structure in Moldova, is provided in annexes to this report. Six sectors were selected for analysis based on their contribution to the Moldovan GDP (at the stage of the inception report), their shares of employment and exports, the registered number of SMEs, and their potential for growth. This report provides key findings from consultations across these six sectors. Detailed reports for each of the six sectors are available as a separate document. Secondary data and research included open online sources, including the website of the National Bureau of Statistics.